Yolanda Bender, Back Pain - Ralitsa Akins (Association of American Medical Colleges, 2012)
Abstract This is an OSCE case. Ms. Yolanda Bender, a 45-year old coordinator, comes to ambulatory clinic with complaint of low back pain that radiates to the right leg. She has had similar pain on and off for the last several years but it has never been so severe. Now she can hardly walk, trying not to use much her right leg. Last Monday, she was helping a co-worker move to a new office and felt an abrupt pain in her lower back. Since then Ms. Bender has been trying not to move much; she rested during the weekend and felt better; she went to work on Monday through Thursday, but on Friday the pain was so severe that she had to stay at home. Ms. Bender is obviously in pain, leaning slightly to the right, with her right leg slightly flexed. She tried Ibuprofen for her pain but it does not help much; her pain today is 8-9/10. Since Friday, the pain goes down the side of her right leg, down to her foot. Patients with low back pain, as the one described in this case, are often seen first in the primary care setting. It is important for the medical students to get acquainted with the approach to such patients, both in history taking and physical examination. This case was used for clinical skills exam of 100 students over two academic years with two cohorts of students (students in integrated curriculum and students in traditional medical curriculum); case statistics were calculated and found to be of good discrimination quality for future use in OSCE exams.